Vagus Nerve Cross-Sectional Area in Patients With Parkinson's Disease—An Ultrasound Case-Control Study - Horsager, Jacob; Walter, Uwe; Fedorova, Tatyana D.; Andersen, Katrine B.; Skjærbæk, Casper; Knudsen, Karoline; Okkels, Niels; von Weitzel-Mudersbach, Paul; Dyrskog, Stig Eric; Bergholt, Bo; Borghammer, Per (Frontiers in Neurology, 2021)
Background: Vagal parasympathetic neurons are prone to degeneration in Parkinson's disease (PD). High-resolution ultrasound can precisely estimate the cross-sectional (CSA) area of peripheral nerves. Here, we tested the hypothesis that vagus CSA is reduced in PD. Methods: We included 56 healthy controls (HCs) and 63 patients with PD. Using a high-end ultrasound system equipped with a high-frequency transducer, five images were obtained of each nerve. The hypoechoic neuronal tissue was delineated offline with dedicated software and the CSA extracted. Results: In the initial PD vs. HC comparison, no statistically significant differences were observed in mean left vagus CSA (HC: 1.97 mm2, PD: 1.89 mm2, P = 0.36) nor in mean right vagus CSA (HC: 2.37 mm2, PD: 2.23 mm2, P = 0.17). The right vagus CSA was significantly larger than the left vagus CSA in both groups (P < 0.0001). Females were overrepresented in the HC group and presented with generally smaller vagus CSAs. Consequently, sex-adjusted CSA was significantly smaller for the right vagus nerve of the PD group (P = 0.041), but not for the left. Conclusion: A small but significant reduction in sex-adjusted right vagus CSA was observed in patients with PD. The left vagus CSA was not significantly reduced in patients with PD. Ultrasound may not be a suitable method to detecting vagal axonal loss in individual patients.